Characterisation of Antiviral Activity of Cathelicidins from Naked Mole Rat and Python bivittatus on Human Herpes Simplex Virus 1 - Alexia Damour; Magali Garcia; Hye-Sun Cho; Andy Larivière; Nicolas Lévêque; Chankyu Park; Charles Bodet (Pharmaceuticals, 2021)
Hg-CATH and Pb-CATH4 are cathelicidins from Heterocephalus glaber and Python bivittatus that have been previously identified as potent antibacterial peptides. However, their antiviral properties were not previously investigated. In this study, their activity against the herpes simplex virus (HSV)-1 was evaluated during primary human keratinocyte infection. Both of them significantly reduced HSV-1 DNA replication and production of infectious viral particles in keratinocytes at noncytotoxic concentrations, with the stronger activity of Pb-CATH4. These peptides did not show direct virucidal activity and did not exhibit significant immunomodulatory properties, except for Pb-CATH4, which exerted a moderate proinflammatory action. All in all, our results suggest that Hg-CATH and Pb-CATH4 could be potent candidates for the development of new therapies against HSV-1.